PERBANDINGAN CUCI TANGAN BEDAH DENGAN DAN TANPA SIKAT TERHADAP KESTERILAN TANGAN PERAWAT BEDAH DI INSTALASI BEDAH SENTRAL RSUD TAMAN HUSADA BONTANG - Andra Frastya; Diah Setiani; Tini (Bajang Institute, 2024)
Introduction:Surgical room staff have their own hand washing procedure, namely sterile hand washing or better known as Surgical Scrub before carrying out surgery.The operating room staff at Taman Husada Bontang Hospital carry out sterile hand washing procedures before surgery using filtered water, with antiseptic fluid containing 4% chlorhexidine and following the steps for sterile hand washing procedures but do not use a nail brush. Method:This research uses a Quasi Experimental Nonequivalent control design method. The research subjects consisted of 16 surgical nurses at the Central Surgical Installation of Taman Husada Bontang Regional Hospital by taking swabs of the skin of the palms using sterile cotton swabs, cultured on blood agar media and incubated for 24 hours, then counted the bacterial colonies that grew on the media and analyzed the difference. Results: There is a pre test post test difference in surgical hand washing without a brush with a p value of 0.018 using the Wilcoxon test and there is a pre test post test difference in surgical hand washing with a brush with a p value of 0.012 using the Wilcoxon test. Meanwhile, there was no difference between washing surgical hands with and without a brush, there was no difference in the sterility of the hands of surgical nurses in the surgical hand washing group without a brush and surgical hand washing with a brush with a p value of 0.904 using the independent t test. Conclusion: There is no difference between washing surgical hands with and without a brush on the sterility of surgical nurses' hands in the Central Surgical Installation of Taman Husada Bontang Hospital.